4H-pyranylidene organic dyes for dye-sensitized solar cells: Twisted structures towards enhanced power conversion efficiencies. (15th November 2019) - Andrés-Castán, José María; Andreu, Raquel; Villacampa, Belén; Orduna, Jesús; Franco, Santiago
Graphical abstract: Highlights: The highest efficiency for a 4H -pyranylidene was obtained. High Open Circuit Voltage (Voc) without the use of additives. An off-plane thiophene ring minimizes aggregate formation. The incorporation of an additional thiophene ring increases stability of the dyes. Abstract: Five sensitizers bearing a 4H -pyranylidene moiety have been synthesized. The incorporation of a thiophene ring (with different substituents in its position 5), in the exocyclic double bond of the previously reported SFO-346, leads to twisted structures of type 2D-π-A and D–(π–A)2 that minimize the π-π stacking of the dyes on the photoanode. Theoretical calculations confirm the tridimensional structure of the molecules. Moreover, the different electronic nature and bulkiness of the substituents modulate the optical and electrochemical properties of the sensitizers. A power conversion efficiency of 7.68% was obtained when the thiophene was substituted with a tert -butyl group (dye 16 ), the highest value reported, so far, for dyes based on a 4H -pyranylidene. That efficiency is mainly due to the high open circuit voltage observed (0.729 V) without using anti-aggregating additives.